Deformation of Alkali-Activated Materials at an Early Age Under Different Curing Conditions - Češnovar, Mark; Traven, Katja; Ducman, Vilma (Frontiers in Chemistry, 2021)
The production of alkali-activated materials (AAM) is known for its environmentally friendly processing method, where several amorphous-rich aluminosilicate materials sources combine with an alkali media solution to form solid, ceramic-like materials. In terms of the Si:Al, Na(K):Al, and Na(K):H2O ratios, the theory of AAM formation is quite well developed, but some open questions in the technology process remain, especially with regards to the means of curing, where the generation of defects can be persistent. Knowing that deformation is extremely high in the early ages, this study investigates the effects of temperature and moisture on shrinkage behavior within the first 72 hours, of AA pastes made from ladle (LS) and electric arc furnace (EAF) slag and activated by sodium silicate (Na2SiO3). The method to determine the deformation of alkali-activated slag-based materials, in terms of both autogenous and drying shrinkage, was based on the modified ASTM C1698 – 19 standard for the measurement of autogenous shrinkage in cement pastes. Autogenous deformation and strain were measured in four samples, using the standard procedure at room temperature, 40 and 60 °C. Furthermore, using an adjusted method, nine samples were characterized for strain and partial surface pressure, while drying at room temperature, 40, or 60 °C at a relative humidity of 30 or 90 %. The results show that the highest rate of autogenous shrinkage occurred at a temperature of 60 °C, followed by drying shrinkage at 60 °C and 30 % relative humidity, owing to the fact that the rate of evaporation was highest at this moisture content. The study aims to provide guidance regarding selection of the optimal curing set in order to minimize deformations in slag-based alkali-activated materials. In the present case, curing at a temperature of around 40 °C under lower moisture conditions for the first 24 h provided optimal mechanical properties for the slags investigated. The methodology might also be of use for other aluminosilicate sources such as metakaolin, fly-ash, and mineral-wool-based alkali-activated materials.